Stategies For Reducing Substance Abuse Among Street Children: A Systematic Review - Irawan Faisal Adi; Ferry Efendi; Praba Diyan Rachmawati (Universitas Pahlawan Tuanku Tambusai, 2026)
Introduction: Substance abuse among adolescents, particularly street children, is a global public health concern influenced by demographic and social factors. While substance abuse in school settings has been widely studied, evidence focusing on street children remains limited. This review aims to evaluate strategies for reducing substance abuse among street children, with an emphasis on interventions affecting physical, mental, and social well-being. Method: This systematic review followed PRISMA 2020 guidelines and was registered in PROSPERO. Literature searches were conducted in four databases (Scopus, Web of Science, PubMed, and ProQuest), yielding 8,774 records. After screening and eligibility assessment, eight studies published between 2016 and 2025 were included. Study quality was appraised using the JBI critical appraisal tool, and findings were synthesized narratively. Results: Eight studies involving homeless or street-involved adolescents aged 10–19 years were reviewed. Commonly reported substance use included alcohol, cannabis, and inhalants. Interventions such as motivational interviewing, psychological reinforcement, and strength-based approaches were effective in reducing risky behaviors and increasing readiness for change. Conclusion: Motivational interviewing combined with community-based psychosocial support is effective in addressing substance abuse among high-risk adolescents. Sustainable interventions should be holistic and adapted to local cultural and structural contexts.